Cancer mortality among electric utility workers exposed to polychlorinated biphenyls. Issue 10 (October 1997) - Loomis, D; Browning, S R; Schenck, A P; Gregory, E; Savitz, D A
Abstract : OBJECTIVES: To assess whether excess mortality from cancer, malignant melanoma of the skin, and cancers of the brain and liver in particular, is associated with long term occupational exposure to polychlorinated biphenyls (PCBs). METHODS: An epidemiological study of mortality was conducted among 138, 905 men employed for at least six months between 1950 and 1986 at five electrical power companies in the United States. Exposures were assessed by panels composed of workers, hygienists, and managers at each company, who considered tasks performed by workers in 28 job categories and estimated weekly exposures in hours for each job. Poisson regression was used to examine mortality in relation to exposure to electrical insulating fluids containing PCBs, controlling for demographic and occupational factors. RESULTS: Neither all cause nor total cancer mortality was related to cumulative exposure to PCB insulating fluids. Mortality from malignant melanoma increased with exposure; rate ratios (RRs) relative to unexposed men for melanoma were 1.23 (95% confidence interval (95% CI) 0.56 to 2.52), 1.71 (0.68 to 4.28) and 1.93 (0.52 to 7.14) for men with < 2000, > 2000-10, 000, and > 10, 000 hours of cumulative exposure to PCB insulating fluids, respectively, without consideration of latency. Lagging exposure by 20 years yielded RRs of 1.29 (0.76 to 2.18), 2.56 (1.09 to 5.97), and 4.81 (1.49 to 15.50) for the same exposure levels. Mortality from brain cancer was modestly increased among men with < 2000 hours (RR 1.61, 95% CI 0.86 to 3.01) and > 2000-10, 000 hours exposure (RR 1.79, 95% CI 0.81 to 3.95), but there were no deaths from brain cancer among the most highly exposed men. A lag of five years yielded slightly increased RRs. Mortality from liver cancer was not associated with exposure to PCB insulating fluids. CONCLUSIONS: This study was larger and provided more detailed information on exposure than past investigations of workers exposed to PCBs. The results suggest that PCBs cause cancer, with malignant melanoma being of particular concern in this industry.